Spicy Snacks, Sweet Prices: How Does Brand Image Determine Consumer Choices? - Sihombing, Elisabet (Bulletin of Management and Business, 2023)
This study aims to analyze the effect of price on purchase intention mediated by brand image among consumers of XYZ spicy snack products in Malang City. In the highly competitive snack industry in Indonesia, price and brand image play an important role in influencing consumer behavior. This study explores how brand image can act as a mediating factor that strengthens the relationship between price and purchase intention. An explanatory quantitative approach was used in this study by distributing questionnaires to 60 consumers selected through a purposive sampling technique. Data were analyzed using the Partial Least Squares method with the help of SmartPLS 4.0 software. The results showed that price has a limited direct effect on purchase intention, but has a significant impact on brand image. Brand image, in turn, has a strong and positive influence on purchase intention. Furthermore, brand image significantly mediates the relationship between price and purchase intention. These findings suggest that XYZ spicy snack products should not only focus on affordable pricing strategies but also on enhancing brand image to drive consumer purchasing decisions more effectively.